Human spaceflight : from Mars to the stars - Friedman, Louis (The University of Arizona Press, 2015)
"This book explores the future of human presence in space and the possibility of interstellar travel beyond Mars. Friedman offers viable, cost effective, and intriguing insights into current and future technologies that could expand humanity's concept of not only life on Earth but also life in space"--Provided by publisher